Ruling determination of Genetically Modified Foods (GMF) in Islam - Mohd Izhar Ariff Mohd Kashim,; Mohd Helmy Mokhtar,; Nur Asmadayana Hasim,; Farah Ayuni Mohd Hatta, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The analysis in this article highlighted the essence of the principle of ruling determination of genetically modified foods (GMF) products in Islam based on the framework of Maqasid Syariah. GM food is a modern food product presently multiplying in the world demand. It is yielded through biotechnological engineering to manipulate plants’ and animals’ deoxyribonucleic acid (DNA). As a result of the process, there will be food products claimed to be more nutritious because they contain more nutrients than the original products. These GMF products can also be farmed in large quantities and involve minimal cost compared to foods that do not undergo genetic modification. Nevertheless, the products produced still do not have any ruling guidelines for Muslims to be used as a backup. Therefore, this research intended to produce guidelines for determining the ruling of foods that have undergone the process of biotechnological engineering. Furthermore, this study aspired to explain the importance of the guidelines for determining the ruling of genetically modified foods (GMF) to Muslims. In order to complete this study, data collection methods were conducted using qualitative design through descriptive and comparative data collection methods and content analysis of fiqh and scientific sources. The conclusion verified that GM food products could be consumed if they comply with the principles that have been outlined.